Desenvolvimento de um smart plug para controle e monitoramento de aparelhos elétricos utilizando o conceito de internet das coisas - Diógenes, Daniel Pablo Dantas (2019)
The improvement in the management of energy resources depends on the amount of information that is passed on to the user, being of great importance the measures of power, consumption and financial cost. The residences are equipped with energy meters, however these belong to the local concessionaire, so that the consumer does not have access to the measured data, only consumption and billing at the end of each month. The control of loads becomes more complicated, since there already exist devices with such function, but that do not have the function of reading of data or have a complex installation. Considering the growing trend in the use of applications and smartphones, and the very expansion in the concept of the internet of things, an equipment that is able to monitor and control other elements and send their information to the internet becomes a necessity to the consumer. The main objective of this work is to develop a smart plug with the ability to read and control electrical devices connected to it. The project was motivated with the objective of facilitating access to the electrical information of any appliance connected to single-phase sockets and to allow the control of the load through timing or manual activation. The smart plug proposal was made using precision components used in commercial equipment such as current transformers, potential transformers and the ADE7753 measurement integrated circuit, aiming at a good precision of the final product. The information obtained from the power grid and the equipment activation and shutdown commands were passed on to the customer in real time through an application dedicated to this purpose, presenting three activity environments, aimed at reading data and remote commands. The communication was performed using the MQTT protocol in conjunction with the Wi-Fi module ESP8266-01. The results of the tests showed that the smar plug presented an overall error of 2%, being with a good level of accuracy compared to commercial equipment, communication through the application was effective, allowing access to the information through the mobile phone. Load control and timing have also proved possible, allowing you to remotely trigger or trigger a specific device